The use of running and jumping exercises in special motor training of young forwards 13-14 years old - Yaroslav Kraynik; Vyacheslav Mulyk; Volodimir Perevoznik; Svyatoslav Koval (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to determine the effect of using complexes of various athletics running and jumping exercises on the indicators of the quantity and quality of technical and tactical motor actions of young forwards-football players 13-14 years old. Material & Methods: the study involved forwards-football players of the children and youth football club Arsenal in Kharkiv from May to October 2019. As the initial data of technical and tactical motor actions, we used the indicators obtained by football players during 10 games of the previous competitive period (May-October 2018). In the preparatory period, complexes of special athletics exercises were used for young football players of the 13-14 years old research group in each training session, which were held 4 times a week, the control group carried out the training process according to the Youth Sports School program, in which classes were also held 4 times a week for 90 minutes. Results: the study made it possible to establish the influence of athletics running and jumping exercises on the special motor fitness of young forwards-football players 13-14 years. Conclusions: the use of specialized athletics running and jumping exercises for young forwards-football players attacking 13-14 years during the preparatory period allowed us to improve the results of indicators of the quantity and quality of performing motor and technical and tactical actions.